2020
DOI: 10.3389/fphar.2020.00073
|View full text |Cite|
|
Sign up to set email alerts
|

Iguratimod as a New Drug for Rheumatoid Arthritis: Current Landscape

Abstract: Iguratimod (IGU) is a novel synthetic small molecule disease modified anti-rheumatic drug approved only in Japan and China up to date. IGU plays an important immunomodulatory role in the synovial tissue of rheumatoid arthritis by inhibiting the production of immunoglobulins and cytokines and regulating T lymphocyte subsets. IGU also regulates bone metabolism by stimulating bone formation while inhibiting osteoclast differentiation, migration, and bone resorption. In clinical trials, IGU was shown to be superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 45 publications
(46 reference statements)
0
34
0
Order By: Relevance
“…Iguratimod, also named T-614 (3-formylamino-7-methylsulfonylamino-6-phenoxy-4H-1-benzopyran-4one), has been considered to be a novel immunomodulator and widely used to treat RA by rheumatologists in China and Japan [39][40][41]. In present study, we observed the effect of iguratimod on RIF in LN.…”
Section: Discussionmentioning
confidence: 50%
“…Iguratimod, also named T-614 (3-formylamino-7-methylsulfonylamino-6-phenoxy-4H-1-benzopyran-4one), has been considered to be a novel immunomodulator and widely used to treat RA by rheumatologists in China and Japan [39][40][41]. In present study, we observed the effect of iguratimod on RIF in LN.…”
Section: Discussionmentioning
confidence: 50%
“…It could alleviate joint damage and immune abnormalities in chronic arthritis and autoimmune diseases; inhibit inflammatory cytokines (IL-1, IL-6, IL-8, and TNF) production; block the IL-17 signalling pathway and inhibit lymphocyte proliferation and immunoglobulin production ( 10 ). In terms of clinical manifestations, Iguratimod could significantly reduce the levels of ESR, C-reactive protein, immunoglobulin, IL-1, IL-6, TNF and other inflammation diagnostic parameters ( 7 , 11 ). Moreover, in clinical studies, the safety and effectiveness of Iguratimod have been verified in patients with rheumatoid arthritis ( 12 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iguratimod, also known as T-614, is a new type of small molecule compound with anti-inflammatory and immunomodulatory effects; It was listed in China (2011) and Japan (2012) for the treatment of rheumatoid arthritis; its safety and effectiveness have been verified in patients with rheumatoid arthritis ( 6 ). As Iguratimod could inhibit the production of inflammatory cytokines, such as IL-1 and TNF; block the IL-17 signalling pathway and inhibit cyclooxygenase ( 7 ), Iguratimod may be effective in the treatment of SPA/AS. However, no rigorous clinical research exists to confirm this speculation.…”
Section: Introductionmentioning
confidence: 99%
“…Iguratimod, a disease modified anti-rheumatic drug (DMARD) is known to inhibit the production of immunoglobulins and cytokines and regulate T lymphocyte subsets at the synovial joints [ 197 ]. Iguratimod was also reported [ 198 ] to inhibit nuclear translocation of NF-κB p65.…”
Section: Molecules That Can or May Be Repurposed As Nf-κb Pathway mentioning
confidence: 99%